An application of SGA: How urban resident acts in making traveling decisions - Long Chenxu; Li Jing; Li Zhuyi (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: To study how urban resident acts in making traveling decisions. Design/methodology/approach: Simple Genetic Algorithm (SGA) Findings: Using SGA to make the model of urban resident's decisions is rational. Research limitations/implications: This study is just about single one and the SGA could be made better. Originality/value: Use SGA to describe urban resident's traveling behavior, and combine the management problem with the AI.
Keywords: 650; urban resident; traveling decision; SGA